Designing learning with embodied teaching : perspectives from multimodality - Lim, Fei Victor (Abingdom, Oxon ; New York, NY : Routledge, 2021)
"Teaching and learning involve more than just language. The teacher's use of gestures, the classroom spaces she occupies and the movements she makes, as well as the tools she uses, work together with language, as a multimodal ensemble of meanings. Embodied teaching is about applying the understandings from multimodal communication to the classroom. It is about helping teachers recognise that the moves that they make and the tools that they use in the classroom are part of their pedagogy and contribute to the design of the students' learning experience. In response to the changing profile and needs of learners in this digital age, pedagogic shifts are required. A shift is the evolving role of teachers from authority of knowledge to designers of learning. This book discusses, with examples, drawn from case-studies, on how teachers can use corporeal resources and (digital) tools to design learning experiences for their students. It advances the argument that the study of the teacher's use of language, gestures, positioning and movement in the classroom from a multimodal perspective can be productive. This book is intended for educational researchers, teacher practitioners as well as curriculum specialists and policy makers. The central proposition is that as teachers develop a semiotic awareness of how the choices made in their use of various meaning-making resources express their unique pedagogy, they can use these multimodal resources with aptness and fluency to design meaningful learning experiences. This book also presents a case for further research in educational semiotics to understand the embodied ways of meaning-making in the pedagogic context"--
OCLC-licensed vendor bibliographic record.
Keywords: Communication in education; Interaction analysis in education; LANGUAGE ARTS & DISCIPLINES / Linguistics; Embodied teaching